2009
DOI: 10.1007/s00442-009-1340-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral archives link the chemistry and clonal structure of trembling aspen to the food choice of North American porcupine

Abstract: Understanding the links among plant genotype, plant chemistry, and food selection by vertebrate herbivores is critical to assess the role of herbivores in the evolution of plant secondary chemistry. Some specialized vertebrate herbivores have been shown to select plants differentially according to plant genotype, but examples from generalists, which constitute the vast majority of vertebrate herbivores, are few, especially in natural conditions. We examined the relationship between the North American porcupine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Both voles and deer selectively attacked different O. biennis genotypes in our study (Fig. 4), supporting a growing body of literature showing that generalist vertebrates can feed selectively among genotypes within a species, including voles (Pusenius et al 2002), beavers (Bailey et al 2004), hares (Laitinen et al 2004), porcupine (Diner et al 2009), deer (Duncan et al 2001) and moose (Jia et al 1997). More importantly, selective feeding in our study differentially influenced genotype fitness and resulted in natural selection for plant traits.…”
Section: Discussionsupporting
confidence: 86%
“…Both voles and deer selectively attacked different O. biennis genotypes in our study (Fig. 4), supporting a growing body of literature showing that generalist vertebrates can feed selectively among genotypes within a species, including voles (Pusenius et al 2002), beavers (Bailey et al 2004), hares (Laitinen et al 2004), porcupine (Diner et al 2009), deer (Duncan et al 2001) and moose (Jia et al 1997). More importantly, selective feeding in our study differentially influenced genotype fitness and resulted in natural selection for plant traits.…”
Section: Discussionsupporting
confidence: 86%
“…This increased pressure is likely driven by mammals rather than by insects because mammals can take advantage of the very young sprouts' short stature during a brief window of opportunity. Previous studies have shown phenolic glycosides to reduce the preference or performance of several mammals (Wooley et al, 2008;Diner et al, 2009) and insects (Hwang and Lindroth, 1998;Lindroth, 2001, 2004;Donaldson and Lindroth, 2007). Fewer studies have revealed antiherbivore properties of condensed tannins (Ayres et al, 1997), but see Donaldson and Lindroth (2004) and Bailey et al (2004).…”
Section: Discussionmentioning
confidence: 95%
“…Insect herbivores include outbreak species such as the forest tent caterpillar, gypsy moth, and large aspen tortrix (Mattson et al, 1991), while mammalian herbivores include beaver, deer, elk, hare, moose, and porcupine (Perala, 1990;Diner et al, 2009). Many studies have shown antiherbivore properties of phenolic glycosides against both insects Lindroth, 2001, 2004;Donaldson and Lindroth, 2007) and mammals (Wooley et al, 2008;Diner et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is essential to understand how food quality influences foraging decisions and constrains population persistence of wildlife for effective conservation management (Rothman 2015 (Snyder 1992, Diner et al 2009, Nie et al 2015 and omnivores (Kimball et al 1998) in different ecosystems. A major outcome of this study is an insight into how and why koalas use habitats and food tree species under different rainfall conditions in semi-arid regions.…”
Section: Synthesismentioning
confidence: 99%